Structural effects and lipid membrane interactions of the pH-responsive GALA peptide with fatty acid acylation - Lin, Brian; Missirlis, Dimitris (Biochemistry, 2012)
GALA is a pH-responsive, membrane-perturbing peptide designed to fold from a random coil at physiological pH to an amphipathic α-helix under mildly acidic conditions. Because of its pH-activated function, GALA has been sought-after as a component of intracellular drug delivery systems that could actively propel endosomal escape. In this study, we conjugated GALA with lauryl and palmitoyl fatty acid tails as model hydrophobic moieties and examined the physicochemical characteristics and activities of the resulting peptide amphiphiles (PAs). The fatty acid variants of GALA exhibited distinctly different membrane perturbing mechanisms at pH 7.5 and 5.5. At physiological pH, the PAs ruptured liposomes through a surfactant-like mechanism. At pH 5.5, lauryl-GALA was shown to form transmembrane pores with a higher potency as compared to its unmodified peptide counterpart; however, after prolonged exposure it also caused liposome lysis. The lytic activity of fatty acid-conjugated GALA did not impair cell viability. Lauryl-GALA was tolerated well by SJSA-1 osteocarcinoma cells and enhanced cell internalization of the PA was observed. Our findings are discussed with the overarching goal of developing efficient therapeutic delivery systems.
Gesehen am 10.11.2018